(untitled) (Comparatismi, 2025)
The article aims to provide a mapping of the complex contemporary theories that seek to redefine the genre of the novel within the political, historical, and economic dynamics of globalization and decolonization. The historical opposition between the Auerbachian mimetic tradition (the tradition of Waterloo) and the Bakhtinian multidiscursivity (the tradition of La Mancha) seems to resurface today in the tension between a global novel that follows the forms of chronicle and non-fiction, and a transcultural, multilingual worldly-novel more closely tied to the modes of the real maravilloso. These stylistic and ontological differences then resonate in the model of the world represented: on the one hand, the borderless globe of capitalism; on the other, the relational and decolonial worldliness among localities.